2010
DOI: 10.3998/ark.5550190.0011.911
|View full text |Cite
|
Sign up to set email alerts
|

Condensed phase conformational isomerization of 5-[3-(1,3-dioxo-1,3-dihydro-isoindol-2-yl)-propoxy]-3-methyl-1H-pyrazole-4-carboxylic acid methyl ester

Abstract: Presence of ester group adjacent to methyl group in a pyrazole ring system results in a flexible hydrogen bond. This bond can be freely rotate to generate the conformational isomers. Conformational isomers can be separated if the barrier to rotation or the energy difference between the two configurations is large. In the present study, in solution state, this spinning is so fast that it was difficult to predict the conformational change whereas the condensation of molecules in solid state, existence of two con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The conformation of the ester group, linking the two aromatic systems, is anti-periplanar with torsion angles c(C2 0 -O2-C3-C1 0 ) between 1718 and 1768. These results are in agreement with the preferred Z conformation found in the ester group O3C3O2C2 0 [2][3][4][5][6] and also predicted by theoretical calculations (see above). However, there is a strong twist in the ester part with respect to the C-O single bond (Fig.…”
Section: -Naphthoates 1-7supporting
confidence: 92%
See 2 more Smart Citations
“…The conformation of the ester group, linking the two aromatic systems, is anti-periplanar with torsion angles c(C2 0 -O2-C3-C1 0 ) between 1718 and 1768. These results are in agreement with the preferred Z conformation found in the ester group O3C3O2C2 0 [2][3][4][5][6] and also predicted by theoretical calculations (see above). However, there is a strong twist in the ester part with respect to the C-O single bond (Fig.…”
Section: -Naphthoates 1-7supporting
confidence: 92%
“…Torsion C angle refers to the preferred conformation around the C(O)-O-R ester function. As described above, the Z conformation of esters is expected to be more stable than the E conformation [2][3][4] (Chart 1). In a previous work, phenyl esters of cinnamic acid showed that the Z conformation was 4.91 kcal mol À1 more stable than its E counterpart.…”
Section: Theoretical Calculationsmentioning
confidence: 89%
See 1 more Smart Citation